The education system as an instrument of construction of national identity (Journal of Educational Sciences, 2016)
Based on using of the constructivist and interpretive approaches and method of discourse analysis this study focus on the investigation of the content of the school textbooks for primary school in the frame of the course “Me and Ukraine” (for pupils of 1-4 grades of elementary school). The results of the research showed that specifi c discourses are transmitted through the school education – the discourse of patriotism, civic responsibility, national heroes, etc. – and by such discourse national identity is constructed. In contemporary Ukraine there is blurred perception about the “content” of the Ukrainian national identity. It can be also traced in the early stages of identity formation – in school education, where school textbooks contain elements of both versions of nation-building – ethnonation and civic nation.
Keywords: national identity; school textbook; education; image of Ukraine; ethno-nation; political nation.